Aplikasi Parkir Menggunakan Ionic Framework dan Firebase - Natalia Chandra; Kelvindo Sutan; Christian Antonious; Christian Handoko (Engineering, MAthematics and Computer Science (EMACS) Journal, 2019)
Jakarta as the capital of the Republic of Indonesia as well as being the largest city in Indonesia. The high number of Jakarta residents as well as the increase in the number of vehicles has become a potential congestion in certain areas, such as shopping centers, because the high value of transactions in parking management services has resulted in long queues. There are several problems that often occur in the parking area, as for the problem is the number of vehicles that want to park exceeds the parking capacity, long queues at the door of payment on weekends, it is difcult to contact vehicle owners who vehicles have problem. One of them is through this research which aims to develop a Hybrid mobile-based online parking payment application. The application of the application is expected to be a solution for users in the parking transaction process through the virtual money system as a parking payment tool and provide applications that can notify vehicle owners who have problems. The methodology applied in this research is by analyzing prospective users and analyzing similar applications.